Effect of Enzymatic pre-treatment of microalgae extracts on their anti-tumor activity - Jabeen, Asma (Biomed J, 2017)
BACKGROUND: There is an increasing need to find natural bioactive compounds for pharmaceutical applications, because they have less harmful side effects compared to their chemical alternatives. Microalgae (MA) have been identified as a promising source for these bioactive compounds, and this work aimed to evaluate the anti-proliferative effects of semi-purified protein extracted from MA against several tumor cell lines. METHODS: Tested samples comprised MA cell extracts treated with cellulase and lysozyme, prior to extraction. The effect of dialysis, required to remove unnecessary small molecules, was also tested. The anti-cancer efficacies of the dialyzed and undialyzed extracts were determined by measuring cell viability after treating four human cancer cell lines, specifically A549 (human lung carcinoma), MCF-7 (human breast adenocarcinoma), MDA MB-435 (human melanoma), and LNCap (human prostate cancer cells derived from a metastatic site in the lymph node). This was compared to the effects of the agents on the human BPH-1 cell line (benign human prostate epithelial cells). The t-test was used to statistically analyze the results and determine the significance. RESULTS: Against LNCap and A549 cells, the performance of cellulase-treated extracts was better (with p-values < 0.05, as compared to the control) than that of lysozyme-treated preparations (with p-values mainly > 0.05, as compared to the control); however, they had similar effects against the other two tumor cell lines (with p-values mainly < 0.05, as compared to the control). Moreover, based on their effect on BPH-1 cells, extracts from lysozyme-treated MA cells were determined to be safer against the benign prostate hyperplasia cells, BPH-1 (with p-values mainly > 0.05, as compared to the control). After dialysis, the performance of MA extracts from lysozyme-treated cells was enhanced significantly (with p-values dropping to < 0.05, as compared to the control). CONCLUSIONS: The results of this work provide important information and could provide the foundation for further research to incorporate MA constituents into pharmaceutical anti-cancer therapeutic formulations.